The impact of TikTok on consumers’ purchase intentions - Grabowska Justyna; Jaciow Magdalena; Strzelecki Artur (Journal of Economics and Management)
Aim/purpose – This study investigates how TikTok influences consumers’ purchase intentions by examining the relationships among key factors, including habit, intelligent recommendation, perceived ease of use, perceived cost, perceived usefulness, attitude, and social influence. The research aims to integrate aspects of the technology acceptance model (TAM) and the theory of planned behavior (TPB) to offer a comprehensive model of consumer behavior on TikTok, specifically within the Polish market.